Advokasi Pelaksanaan Kegiatan Investing in Nutrition and Early Years (INEY) Fase II di Kota Kupang - Ummi Kaltsum S. Saleh; Wanti; Irfan; Maria Hilaria; Juni Gressilda L Sine; Mareta Bakale Bakoil; Ignasensia Dua Mirong; Margareta Teli; Muhamad Satria Mandala Pua Upa; Bringiwatty Batbual; Asweros Umbu Sogara; Jane Austen Peni; Yualeny Valensia; Namsyah Baso (Rena Cipta Mandiri, 2025)
Stunting has become a national development priority for the Government of Indonesia, including in East Nusa Tenggara (NTT) Province, with a targeted reduction rate of 14% by 2024. Stunting is a manifestation of chronic growth failure in children under the age of five, primarily resulting from prolonged nutritional deficiencies and repeated infections, particularly during the first 1,000 days of life (from conception to two years of age). Children affected by stunting exhibit a height-for-age below the standard growth reference. Beyond its impact on physical stature, stunting also compromises brain development and has long-term consequences on cognitive function and overall productivity.The persistence of stunting is attributed to the insufficient implementation of both specific and sensitive interventions targeting young children and their mothers. The Accelerated Stunting Prevention Program through the Investing in Nutrition and Early Years (INEY) Phase 2 supports catalytic investments aimed at strengthening implementation capacity and systems, while promoting a multisectoral approach to stunting reduction. Advocacy serves as a persuasive communication strategy to influence government stakeholders and local authorities in Kupang City to support the execution of the INEY program. The involvement of Kupang Health Polytechnic (Poltekkes Kemenkes Kupang) is expected to enhance the effectiveness of efforts to reduce the prevalence of stunting in East Nusa Tenggara, particularly in Kupang City.